Feasibility of remote robot empowered teleultrasound scanning for radioactive patients - Ying Liang; Lu Wang; Manuel Escobar Amoresa; Zirui Jiang; Bo Yu; Jiami Li; Man Lu (Scientific Reports)
Abstract To investigate the feasibility of robot-assisted teleultrasound diagnosis for radioactive patients compared with conventional ultrasound diagnosis. In this prospective study (ChineseClinicalTrials.gov identifier, ChiCTR2200057253), 32 radioactive patients were examined by conventional ultrasound and MGIUS-R3 robot-assisted ultrasound from March 2022 to June 2022. After two scans, patients completed a satisfaction survey, including comfort score, fear score, tension score and pain score. The durations of both scans were recorded, and sonographers wore lead apron to prevent the radiation during the conventional examination. Subsequently, the ultrasonic images saved by sonographers were diagnosed and scored. Finally, we evaluated the feasibility of the robot-assisted teleultrasound diagnosis system regarding patients’ satisfaction, examination duration, image quality and diagnostic consistency via χ2 test, Kappa consistency test and Wilcoxon signed-rank test. Among 32 patients (mean age, 54.9 ± 9.8 [SD]; 16 women), 29 had consistent diagnoses and 3 had inconsistent diagnoses between two scans, but the diagnostic consistency was good (Kappa = 0.818, P < 0.001). In addition, there was no statistical difference between two scans with regard to image quality score (29.28 ± 0.47vs29.31 ± 0.44, P = 0.97), comfort score (10vs10, P > 0.99), tension score (0vs0, P > 0.99) and fear score (0.09vs0, P = 0.32). Although 7 patients felt slightly painful during teleultrasound scan, the pain intensity was acceptable (0.31vs0, P = 0.02). The mean duration of teleultrasound examinations was 11.1 min (6–24 min), which was longer than 5.9 min (2–17 min) of conventional examinations (P < 0.001). Comparing robot-assisted teleultrasound and conventional ultrasound, there was no evidence of differences regarding patients’ satisfaction and image quality, and the diagnostic consistency was remarkable.